Comprehensive analysis of the functioning of a university department as a complex system in modern conditions - Meteshkin, K.; Shevchenko, V.; Метешкін, Костянтин Олександрович; Шевченко, Вікторія Олександрівна (Харківський національний автомобільно-дорожній університет, 2025)
This article presents the results of a comprehensive analysis of a university department as a complex system in order to identify weaknesses in the process of administering university departments in conditions of information singularity and crisis phenomena in society.
Комплексний аналіз функціонування кафедри ЗВО як складної системи в сучасних умовах
Keywords: university department; structural analysis; space-time analysis; functional analysis; com- plex system; formalization; кафедра; структурний аналіз; просторово-часовий аналіз; функціональний ана- ліз; складна система; формалізація; 378:001; 10.30977/BUL.2219-5548.2025.108.0.328